The Meridian anthology of restoration and eighteenth-century plays by women (A Meridian book, 1994)
Women playwrights of the Restoration and eighteenth century were bawdy and proper, apologetic and defiant, often derided and occasionally praised. The seven women represented in this groundbreaking anthology - the only collection of Restoration and eighteenth-century plays devoted exclusively to women - had but one thing in common: the desire to ignore convention and write for the stage. In 1660, when theatres in England reopened after years of Puritan repression, women trod the boards as actors for the very first time. By the end of the century they had stormed and breached another bastion of the male domain and become dramatists as well. Most available collections of plays from the period exclude them; traditional criticism overlooks or diminishes them. But their works, as seen here, hold their own against the most popular productions for the theater from 1678 to 1787, and do it with a distinctively female spirit